PENGARUH IKLIM ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KEPALA MADRASAH ALIYAH NEGERI DI EKS KARESIDENAN SURAKARTA The Influence Of Organization Climate And Work Motivation On The Performance Of Principle Of Madrasah Aliyah Negri (State Islamic Senior High School) In Ex-Karesidenan Of Surakarta - Wahab Wahab (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
The performance of the actors in an organization is interrelated with other elements such as the organization’s climate and motivation to work. This research aims to explore the influence of organization’s climate and motivation to work on the performance of madrasah’s (Islamic school) head master. This study uses a correlation survey method, subject of this research is teachers at Madrasah Aliyah Negeri (State Islamic Senior High School) in ex-Karesidenan Surakarta. There are 152 teachers involved in this research as the sample which is selected using cluster stratified proportional random sampling method. Data was gathered through questioners and analyzed using descriptive analysis, simple regression, and double regression. Results show that: (1) generally the average of head-master performances can be categorized as good since they have done their main tasks, (2) the school environment has significantly influence on the head-master performance (71,30%), (3) motivation to work has significantly affected on the head-master performance (73,80%), (4) organization’s climate and motivation to work have influenced on the head master performance (78,70%), (5) motivation to work is the most contributing factor that influence the work of head master (51,60%). Based on these findings, it is necessary to create conducive environment in madrasah, such as designating the right person based on his/her capability, creating a good condition, respecting each other, and appreciating achievement at work